ANALISIS KONDISI SOSIAL EKONOMI PEDAGANG JAGUNG REBUS DI KECAMATAN LUBUK ALUNG (Studi Kasus Pedagang Jagung Rebus di Jalan Raya Lintas Padang Bukittinggi) - Deni Asrul; nofrion Nofrion (JURUSAN GEOGRAFI FIS UNP, 2020)
Abstract This study aims to determine the Analysis of Socio-Economic Conditions of Boiled Corn Traders in Lubuk Alung District. This type of research is quantitative descriptive using primary data as a source of data obtained through interviews, informants in this study were 33 boiled corn traders who were taken in total sampling. Data were analyzed using a percentage formula. The results of this study found that in terms of marriage, the majority of stewed corn traders were married. In terms of education, most of the boiled corn traders have a history of high school education, as many as 19 traders with a percentage of 58%. The economic condition of boiled corn traders, in terms of production costs most of the boiled corn traders have production costs ranging from 2-3 million to 18 the number of traders with a percentage of 55. In terms of income most boiled corn traders have an income of 4-6 million ie as many people traders with a percentage of 46. In terms of profit, the profits obtained by most of the boiled corn traders ranged from 2-3 million, as many as 12 traders with a percentage of 37. In terms of expenditure, most of the education costs ranged from 1-2 million as many as 22 people 67% of traders, and for the cost of daily necessities most of the expenditure of boiled corn traders ranged between Rp. 500,000 - 1,000,000 as many as 15 traders. In terms of the number of dependents, most of the boiled corn traders have dependents 1-2 and 3-4, each with 13 people with a percentage of 43% Keywords: social conditions,economic conditions,boiled corn traders